PENGARUH PUPUK KANDANG SAPI DAN BERBAGAI JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN PADA TANAH GAMBUT - Marbun, Tiurida; Listiawati, Agustina; Zulfita, Dwi (Agros Journal of Agriculture Science, 2024)
Scallions ( Allium fistulosum L.) are a horticultural crop commodity that is worthy of intensive development in Indonesia, especially in Pontianak, West Kalimantan Province. Peat soil has great potential for the development and cultivation of spring onions. Efforts that can be made to overcome the very low availability of nutrients are cow manure. One cultivation technique that can be used to increase leek production is by adjusting plant spacing. This research was carried out on research land located on Jalan Sungai Raya Dalam, Alam Mulia Housing Complex starting on 15 September – 2 November 2023. This research aims to obtain the best dose of cow manure for the growth and yield of leek plants on peat soil and to obtain the best planting distance for the growth and yield of leek plants on peat soil. This research was carried out using a field experimental method with a Split Plot Design pattern , namely: The first factor is the distance between the plants for the main plot: j 1 = 20 cm x 20 cm, j 2 = 20 cm x 25 cm and j 3 = 20 cm x 30 cm. The second factor is cow manure as a sub plot: p 1 = 10 tonnes/ha, p 2 = 20 tonnes/ha and p 3 = 30 tonnes/ha. The observation variables consist of: Root Volume, Plant Dry Weight, Number of Leaves/clump, Plant Height, Number of Saplings/clump and Fresh Weight of the plant. From research that has been carried out, the interaction of using a planting distance of 20 x 25 cm and 10 tonnes/ha of cow manure shows the best growth and yield of leek plants on peat soil.